2020
DOI: 10.1021/acs.jproteome.9b00758
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of the Neuropeptide Level Changes in Dorsal Horn and Dorsal Root Ganglia Regions of the Murine Itch Models

Abstract: Chronic itch can be extremely devastating and, in many cases, difficult to treat. One challenge in treating itch disorders is the limited understanding of the multitude of chemical players involved in the communication of itch sensation from the peripheral to the central nervous system. Neuropeptides are intercellular signaling molecules that are known to be involved in the transmission of itch signals from primary afferent neurons, which detect itch in the skin, to higher-order circuits in the spinal cord and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…peptides, such as proenkephalin-A, proSAAS, protein AF1q, secretogranin-1, thioredoxin and calcitonin gene-related peptide have been detected at measurable level so far, one of which is TAC1 [16]. In the present study, plasma TAC1 levels of sarcoidosis patients and healthy control subjects were found as 1124.25±1117.25 ng/L, 1319.37±1357.38 ng/L, respectively.…”
Section: Discussionsupporting
confidence: 49%
“…peptides, such as proenkephalin-A, proSAAS, protein AF1q, secretogranin-1, thioredoxin and calcitonin gene-related peptide have been detected at measurable level so far, one of which is TAC1 [16]. In the present study, plasma TAC1 levels of sarcoidosis patients and healthy control subjects were found as 1124.25±1117.25 ng/L, 1319.37±1357.38 ng/L, respectively.…”
Section: Discussionsupporting
confidence: 49%
“…Here, quantitation is performed at the MS1 level and the area of the peptide XIC is compared across replicates (53). This method of untargeted NP quantitation has been employed by various groups to study NP profiles in different physiological models, including migraine, chronic itch, and feeding behavior (26,54,55). generated by searching Orbitrap-tandem MS (MS/MS) results for pooled tissues against a peptide database.…”
Section: Label-free Versus Labeled Quantitationmentioning
confidence: 99%